187k views
3 votes
X^2-9x=-2 quadratic equation

User Mikie
by
4.7k points

2 Answers

3 votes

Answer:

x = 9 + sqrt(73) / 2

x = 9 - sqrt(73) / 2

Explanation:

Assuming you want to factor and find its roots:

[Put all the terms in the left hand size]

x^2-9x+2=0

[Use the quadratic formula; Not factorable and too tedious for completing the square]

x = -b +- sqrt(b^2-4ac) / 2a

x = 9 + sqrt(9^2 - 4(1)(2)) / 2(1)

x = 9 - sqrt(9^2 - 4(1)(2)) / 2(1)

x = 9 + sqrt(73) / 2

x = 9 - sqrt(73) / 2

User Srividya
by
5.4k points
2 votes

Answer:

Explanation:

x^2-9x=-2 move the -2 over and set to 0

x^2-9x+2=0

This can not be factored, so use the quadratic formula.

x=9±√73 /2

User Mike Dinsdale
by
4.9k points